Analysis of School Conflicts Involving Parents: Experiences and Resolution - Delio B Sannadan; Claribeth B. San Pedro; Lourdes Myla T. Velchez; Ariel C. Venida (JURNAL INOVATIF ILMU PENDIDIKAN, 2020)
Stakeholders’ partnership in schools is a key factor in delivering a relevant, enabling, and responsible education to the learners. However, in the course of establishing this partnership, conflicts arise inevitably. The main objective of the study was to examine the prevalence of conflicts in schools that involve parents through a document analysis. A total of ten online cases were analyzed and served as the primary sources of data in this study. Coding was done to determine the emerging themes in each case. The analysis revealed that sexual and physical violence committed by a teacher or school official towards the learner; and negligence of duty which resulted in damage to the learner were the common sources of conflict. This suggests that parents’ involvement in the issues is something favorable as apparently parents are expected to be the protectors and defenders of their children especially in times when children’s rights and welfare are at stake or violated. The findings further revealed that in most conflicts, the learners were mostly offended while teachers and school authorities were mostly offenders. This finding suggests that children, even in school or under the custody of the teachers and school authorities, are still vulnerable to any form of violence and danger; and sometimes become helpless and defenseless especially when the persons who they expect to protect them become the aggressors. The finding also revealed that the learners mostly favored the court’s decision. This conveys that in every court ruling, it is still the best interest of the children which is being given the foremost considerations. The implications from the findings of the study may inform the higher authorities in the Department of Education on how such conflicts will be prevented from happening. Also, based on the findings, it is recommended that the education department should take further actions in strengthening the implementation of the Child Protection Policy to keep every learner well-informed of their rights and make every stakeholder aware of their duties and responsibilities in promoting the well-being and education of the learners.Keywords: conflicts, learners, negligence, parents, physical violence, sexual violence.DOI: http://dx.doi.org/10.23960/jiip.v2i2.21817